Inelastic deformation and destruction of fiber-laminated polymer composites in stress concentration zones (Fracture and Structural Integrity, 2020)
The article is devoted to the experimental study of the laws of inelastic deformation of structural polymer composites in the presence of macroinhomogeneous fields. The work uses a three-dimensional optical system and a method of digital image correlation, thermoscanning equipment. The relationship between the selected parameters of the correlation analysis and the scale level of the deformation processes is shown. Experimental data were obtained confirming the presence of a large-scale effect of strength in a certain range of structural parameter values, data on the features of the deformation of composites with various reinforcement schemes, as well as in the presence of technological defects. Recommendations on the use of a video system for calibration and sensitivity assessment of integrated fiber-optic sensors are presented
Keywords: Experimental mechanics; Method of digital image correlation; Stress concentrator; Fiber-laminated polymer composites; The scale effect of strength